Effects of desiccation and rewetting on the release and decomposition of dissolved organic carbon from benthic macroalgae. (15th November 2013) - Wyatt, Kevin H.; Rober, Allison R.; Schmidt, Nicole; Davison, Ian R.
Summary Dissolved organic carbon (DOC) released by benthic algae is an important energy source in shallow aquatic ecosystems. Here, we evaluated the amount, composition and decomposition of DOC released by the benthic macroalga, Cladophora glomerata, during constant hydration and upon rewetting after drying for 0.5, 1, 2, 3 or 6 h on the shoreline of Lake Michigan, U.S.A. Brief desiccation (0.5 h) significantly reduced gross primary productivity (mg C g dry mass−1 h−1) to 0.43 ± 0.13 from 5.66 ± 0.35 for continuously wet algae. When continuously wet, Cladophora filaments released 1.71 ± 0.26 mg DOC g DM−1 h−1 into the surrounding water, representing 30% of carbon fixation; release increased to 7.64 ± 1.08 after 1 h and peaked at 12.18 ± 0.57 after 6 h of drying. Percent extracellular release exceeded carbon fixation upon rewetting after 0.5‐h desiccation and remained above 100% for each time interval thereafter. The composition of exudates changed with time of desiccation. Carbohydrate release increased from 0.84 ± 0.13 to 3.0 ± 0.14 mg g DM−1 h−1 from 0 to 6 h desiccation, but declined as a percentage of total DOC from 49 to 25% over the same time. This reflected the much greater increase in protein yield from 0.40 ± 0.06 mg g DM−1 h−1 for wet algae to 7.70 ± 0.36 at 6‐h desiccation (24 and 63% of total DOC release, respectively). The proportion of carbohydrates to proteins decreased with desiccation time, from 2 : 1 at 0 h to 1 : 2.5 at 6 h. Exudates from constantly hydrated algae (DOC0) and upon rewetting after 6‐h desiccation (DOC6) were degraded by more than 20% over 48 h of incubation inside dark bottles inoculated with the natural microbial community (10% lake water). Both treatments supported an exponential increase in bacterial density, but a greater proportion of DOC0 was used by bacteria after 12 days. Bacterial density increased from 0.09 ± 0.001 to 3.30 ± 0.11 106 cells mL−1 between 0‐ and 12‐day incubation in the DOC0 treatment and from 0.09 ± 0.008 to 2.64 ± 0.10 during the same time period in the DOC6 treatment. Short‐term desiccation results in a substantial release of DOC from Cladophora that is used rapidly by bacteria in the overlying water column. The drying–rewetting cycle could be important for organic matter cycling in freshwater ecosystems where benthic macroalgae occur.